Association between the mental domain of the comprehensive geriatric assessment and prolonged length of stay in hospitalized older adults with mild to moderate frailty - Yu, Yung-Chen; Su, Chien-Chou; Yang, Deng-Chi (Frontiers in Medicine, 2023)
Introduction: Previous researches have shown the risk factors of prolonged length of stay (PLOS) in hospitalized older adults, but it is unclear what are the risk factors of PLOS in hospitalized older adults with mild to moderate frailty. Objective: To identify the risk factors of PLOS in hospitalized older adults with mild to moderate frailty. Methods: We recruited adults aged ≥ 65 years old with mild to moderate frailty admitted to a tertiary medical center in the southern Taiwan from June 2018 to September 2018. Each individual underwent a structural questionnaire interview within 72 hours after admission and 72 hours after discharge. The data were collected face-to-face, including demographic characteristics, comorbidities, length of stay (LOS), and multiple domains of the comprehensive geriatric assessment. The main outcome was PLOS. Results: Individuals who had two or more drugs, were female, did not have cognitive impairment and had a Geriatric Depression Scale score ≥1 had a higher risk of PLOS (probability = 0.81), and these individuals accounted for 29% of the overall study population. Among male individuals younger than 87 years old, those with cognitive impairment had a higher risk of PLOS (probability = 0.76), and among male individuals without cognitive impairment, living alone was associated with a higher risk of PLOS (probability = 0.88). Conclusion: Early detection and management of mood and cognition in older adults, together with comprehensive discharge planning and transition care, may be an important part of reducing LOS in hospitalized older adults with mild to moderate frailty.